EVOLUTION OF THE LEGAL REGULATION OF THE EMPLOYMENT CONTRACT IN THE RUSSIAN LEGISLATION - Natalia S. Zavorokhina; Dmitry V. Treskin; Sofya A. Filiptsova (Russian Studies in Law and Politics)
This article examines the features of the development of labor contract institutions in Russian legislation, examines the stages of the formation of an employment contract, its types and signs.